Synthesis of Titanium Dioxide (TiO2)/Reduced Graphene Oxide (rGO) thin film composite by spray pyrolysis technique and its physical properties. (September 2020) - AlShammari, A.S.; Halim, M.M.; Yam, F.K.; Kaus, N.H. Mohd
Abstract: TiO2 /reduced graphene oxide (rGO) thin films prepared from different GO concentrations (0, 3, 5, and 10 wt%) were successfully deposited on fluorine-doped tin oxide (FTO) glass substrates using spray pyrolysis technique (SPT). The structural, morphological and optical properties of the thin films were examined using Raman spectroscopy and X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and UV–Vis spectroscopy, respectively. The presence of rGO in the thin films structure was confirmed by Raman analysis with D and G band intensity ratios (ID/IG) of 1.01, 1.03 and 1.08 for GO concentrations of 3, 5, and 10 wt%, respectively. The characteristic XRD peaks for TiO2 and rGO at 2ϴ values of 25.3° and 22-23°, respectively, indicate the bonding of TiO2 with rGO. Surface morphology analysis of the TiO2 /rGO thin films reveal homogenous distribution of graphene nanosheets and TiO2 on FTO glass substrate. In addition, optical transmittance reduced from 80% for TiO2 to 45% for TiO2 /rGO prepared with 10 wt% GO. From UV–Vis analysis, band gap energy for TiO2, and TiO2 /rGO reduced from 3.63 eV to 3.38 eV, with increase in the concentration (wt.%) of GO in the thin films. Thus, the use of the SPT method is believed to provide a cost-effective and easy approach to synthesize good quality TiO2 /rGO thin film on FTO glass for photodetector and solar cell applications. Highlights: TiO2 /rGO thin film on FTO glass substrate by spray pyrolysis technique for different ratios of GO colloids. The band gap is shown to decrease with increase in rGO percentage. Raman, Fesem, XRD and UV–Vis spectroscopy analyses confirmed the formation of TiO2 /rGO thin films. Eco-friendly, simple and cost-effective method.